2012
DOI: 10.1029/2012gl052413
|View full text |Cite
|
Sign up to set email alerts
|

Basal crevasses on the Larsen C Ice Shelf, Antarctica: Implications for meltwater ponding and hydrofracture

Abstract: [1] A key mechanism for the rapid collapse of both the Larsen A and B Ice Shelves was meltwater-driven crevasse propagation. Basal crevasses, large-scale structural features within ice shelves, may have contributed to this mechanism in three important ways: i) the shelf surface deforms due to modified buoyancy and gravitational forces above the basal crevasse, creating >10 m deep compressional surface depressions where meltwater can collect, ii) bending stresses from the modified shape drive surface crevassing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
97
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(103 citation statements)
references
References 52 publications
4
97
1
Order By: Relevance
“…This caused temporary changes in its alignment with respect to the large-scale stress field, which might explain part of the slowdown. Other studies have suggested that the presence of marine ice can suppress the speed at which rifts propagate, and several ice shelves such as Larsen C and Filchner-Ronne ice shelves contain rifts that terminate in marine ice-rich suture zones (Glasser et al, 2009;Hulbe et al, 2010;McGrath et al, 2012;Jansen et al, 2013;Borstad et al, 2017). However, very few studies have investigated the relationship between rift tip propagation and fracture toughness of ice directly (see for example Rist et al, 2002) and the dynamics of rift tip propagation remains subject to large uncertainties.…”
Section: Propagation Of the Tip Of Halloween Crackmentioning
confidence: 99%
“…This caused temporary changes in its alignment with respect to the large-scale stress field, which might explain part of the slowdown. Other studies have suggested that the presence of marine ice can suppress the speed at which rifts propagate, and several ice shelves such as Larsen C and Filchner-Ronne ice shelves contain rifts that terminate in marine ice-rich suture zones (Glasser et al, 2009;Hulbe et al, 2010;McGrath et al, 2012;Jansen et al, 2013;Borstad et al, 2017). However, very few studies have investigated the relationship between rift tip propagation and fracture toughness of ice directly (see for example Rist et al, 2002) and the dynamics of rift tip propagation remains subject to large uncertainties.…”
Section: Propagation Of the Tip Of Halloween Crackmentioning
confidence: 99%
“…More recent studies found basal crevasses and channels of various sizes oriented both perpendicular and parallel to the main ice-flow direction at Larsen C, Amery and Getz, Pine Island Glacier, and Fimbul, as well as in Greenland [Luckman et al, 2012;McGrath et al, 2012;Vaughan et al, 2012;Mankoff et al, 2012;Humbert and Steinhage, 2011;Nicholls et al, 2006;Rignot and Steffen, 2008]. The majority of the basal channels reported to date are from ice shelves exposed to ocean waters with a high thermal potential for melting the overlying ice shelf, such as at Pine Island Glacier [Jacobs et al, 2011;Dutrieux et al, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…The base of an ice shelf is a critical interface; basal roughness in the form of channels influences ice-shelf stability [Gladish et al, 2012;McGrath et al, 2012;Vaughan et al, 2012], affects ocean circulation close to the ice base, and plays an important role in modifying the exchange of heat and mass between the ocean and ice shelf [Stanton et al, 2013]. Mapping of the ice basal topography, in most cases, relies on ice surface elevations from satellite altimetry and the freeboard assumption to calculate ice thickness [Pritchard et al, 2012]; thus, basal topography on spatial scales similar or less than the local ice-shelf thickness remains largely unknown for most ice shelves.…”
Section: Introductionmentioning
confidence: 99%
“…Observations have shown that the bending that occurs as ice transitions from resting on land to floating in water (the grounding line) promotes the failure of ice from the bottom up, called basal crevasses, that often appear with characteristic regularity in spacing, persisting within the ice for long distances and eventually promoting the calving of ice (Bindschadler et al, 2011;Glasser and Scambos, 2008;Logan et al, 2013;McGrath et al, 2012;Murray et al, 2015). The main motivation of using DES to understand this phenomenon (or a simplified version thereof) is its rheological flexibility.…”
Section: Experiments: Different Constitutive Models For Icementioning
confidence: 99%